Komitmen terhadap Organisasi di Kalangan Guru-Guru Sekolah Menengah Daerah Bandar Baharu, Kedah - Mohd Othman, Yussoff (1996)
The purpose of this study is to examine the factors related to organizational commitment among secondary school teachers in Bandar Baharu district of Kedah. The objectives of this study were to investigate (a) the relationship between job satisfaction and organizational commitment, (b) the relationship between pay satisfaction and organizational commitment, (c) the relationship between administrative climate and organizational commitment, (d) the differences of organizational commitment among the teachers based on their demographic factors, and (e) the influence of independent variables on organizational commitment. 128 teachers from four secondary schools participated in this study. They represented two service categories, namely graduate teachers and non-graduate teachers. A set of questionnaire containing 57 items using five-points Likert-type scale was applied to measure the teachers' responses. Five main hypotheses and 12 specific hypotheses were constructed for this study. Statistical tools such as using Pearson Correlation t-Test, Analysis Of Variance and Multiple Regression were used to test these hypotheses. The result revealed that (a) there was significant relationship between job satisfaction (intrinsic and extrinsic satisfaction) and organizational commitment, (b) there was significant relationship between pay satisfaction (salary benefit) and organizational commitment, (c) there was significant relationship between administrative climate (personality interaction, and policy) and organizational commitment, (d) organizational commitment was not significantly different among the teachers based on gender, age, job tenure, service categories, service and salary movement, and (e) job satisfaction and salary satisfaction also showed significant influences on the teachers' organizational commitment. Some suggestions have been offered based on these findings, to enhance organizational commitment among teachers.